2015
DOI: 10.1016/j.chb.2014.09.065
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the suitability of student interactions from Moodle data logs as predictors of cross-curricular competencies

Abstract: In the past decades, online learning has transformed the educational landscape with the emergence of new ways to learn. This fact, together with recent changes in educational policy in Europe aiming to facilitate the incorporation of graduate students to the labor market, has provoked a shift on the delivery of instruction and on the role played by teachers and students, stressing the need for development of both basic and cross-curricular competencies. In parallel, the last years have witnessed the emergence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 31 publications
2
40
0
1
Order By: Relevance
“…In fact, only two groups of researchers (Agudo-Peregrina et al, 2014;Gomez-Aguilar et al, 2015) found any statistically significant correlation relationship between student online activity reported in learning analytics and academic performance. More than one researcher confirmed there was no statistically significant relationship between learning analytics, LMS activity data, and student learning outcomes (Iglesias-Pradas, Ruiz-de-Azcarate and Agudo-Peregrina, 2015). Therefore, more studies are needed to test if learning analytics data could relate to or predict student performance.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…In fact, only two groups of researchers (Agudo-Peregrina et al, 2014;Gomez-Aguilar et al, 2015) found any statistically significant correlation relationship between student online activity reported in learning analytics and academic performance. More than one researcher confirmed there was no statistically significant relationship between learning analytics, LMS activity data, and student learning outcomes (Iglesias-Pradas, Ruiz-de-Azcarate and Agudo-Peregrina, 2015). Therefore, more studies are needed to test if learning analytics data could relate to or predict student performance.…”
Section: Introductionmentioning
confidence: 85%
“…The four common units of analysis used with online student activity in learning analytics studies (Agudo-Peregrina et al, 2014;Iglesias-Pradas, Ruiz-de-Azcarate and Agudo-Peregrina, 2015), as outlined below:…”
Section: Learning Analytics Factors and Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last years, we have seen that new areas of study are emerging in the educational domain, for example the Educational Data Mining (EDM) and LA [11]. In general, there are a lot of papers in these domains, focused on course level analysis, predictive models, semantic content analysis, sentimental analysis, and social network analysis, in the general educational context [1], [12], [13], [14], [15], [16], [17], [18], [22], [26], [33].…”
Section: Related Workmentioning
confidence: 99%